2018
DOI: 10.5694/mja17.00726
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine bleeding: managing endometrial dysfunction and leiomyomas

Abstract: Abnormal uterine bleeding refers to any change in the regularity, frequency, heaviness or length of menstruation. There are several potential causes for bleeding disturbance, the two most common being primary endometrial dysfunction and fibroids. Management of abnormal uterine bleeding involves both medical and surgical options and will largely depend on a patient's fertility plans. The use of levonorgestrel-releasing intrauterine devices for heavy menstrual bleeding is increasing in Australia, and they are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
0
10
0
4
Order By: Relevance
“…Hysterectomy is the most definitive treatment for women with refractory disease, particularly when child‐bearing is no longer a consideration . It is estimated that 20% of hysterectomies in Australia are performed for fibroid disease .…”
Section: Surgery For Fibroid Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Hysterectomy is the most definitive treatment for women with refractory disease, particularly when child‐bearing is no longer a consideration . It is estimated that 20% of hysterectomies in Australia are performed for fibroid disease .…”
Section: Surgery For Fibroid Diseasementioning
confidence: 99%
“…6,8 Hysterectomy is the most definitive treatment for women with refractory disease, particularly when child-bearing is no longer a consideration. 3,9 It is estimated that 20% of hysterectomies in Australia are performed for fibroid disease. 10 In addition to being widely accessible and effective, it also has advantages in allowing histologic evaluation of uterine tissue to exclude malignancy.…”
Section: Surgery For Fibroid Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The early stage of endometrial cancer is limited to the endometrial mucosal layer or superficial base layer, but the site of occurrence is often found in the uterine horn, and the traditional curettage is easy to miss curettage, thus missing the diagnosis of endometrial cancer [ 12 ]. If hysteroscopy is adopted, the situation of the entire endometrial can be determined, so hysteroscopy can reduce the occurrence of curettage and leakage in traditional diagnosis and improve the accuracy of endometrial cancer diagnosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%